PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR PADA PABAN III/LATGA SOPS TNI - Januar, Andri; Warman, Yuri; Oktaviana R, Shinta (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
The previously manual system at the Paban III/Latga Sops TNI posed several limitations, such as difficulties in document retrieval, risk of archive loss, and inefficiency in letter management. This study aims to design a structured and computerized information system for archiving incoming and outgoing mail documents. In this research, the software development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and evaluation phases. The result is a web-based system built using PHP programming language and MySQL database, which effectively supports digital management of incoming and outgoing correspondence in a fast and well-documented manner. The system was tested using Black Box method and user acceptance questionnaires, showing that the application met the functional requirements and is feasible for use in the operational environment of Paban III/Latga Sops TNI.